Molecular dynamics simulations of the ligand-binding domain of an N-methyl-D-aspartate receptor. - Kaye, S; Sansom, MS; Biggin, P (2006)
The mechanism of partial agonism at N-methyl-D-aspartate receptors is an unresolved issue, especially with respect to the role of protein dynamics. We have performed multiple molecular dynamics simulations (7 x 20 ns) to examine the behavior of the ligand-binding core of the NR1 subunit with a series of ligands. Our results show that water plays an important role in stabilizing different conformations of the core and how a closed cleft conformation of the protein might be stabilized in the absence of ligands. In the case of ligand-bound simulations with both full and partial agonists, we observed that ligands within the binding cleft may undergo distinct conformational changes, without grossly influencing the degree of cleft closure within the ligand-binding domain. In agreement with recently published crystallographic data, we also observe similar changes in backbone torsions corresponding to the hinge region between the two lobes for the partial agonist, D-cycloserine. This observation rationalizes the classification of D-cycloserine as a partial agonist and should provide a basis with which to predict partial agonism in this class of receptor by analyzing the behavior of these torsions with other potential ligands.